Numerical Simulation of Subfields in a Multi-Tower Concentrated Solar Field - Zaharaddeen Ali Hussaini; Chris Sansom; Peter King; Mounia Karim (SolarPACES Conference Proceedings)
The research introduces an innovative approach to enhancing the efficiency of Multi-tower Concentrated Solar Power (CSP) through a configuration termed Auxiliary Tower with Subfield (ATS). ATS introduces an auxiliary tower and creates a subfield by adding heliostats near its position, aiming to optimize the solar field's optical efficiency and offer modular decentralized power output. ATS configuration employs existing field configurations to pinpoint inefficiencies where an additional tower can be installed, and heliostats are systematically added to the subfields through numerical optimization using various design variables. Although the inclusion of a subfield in the ATS configuration enhances energy output, it does not always offset the additional costs of the auxiliary tower, receiver, and extra heliostats, in small fields. However, when applied to larger fields, starting from 200MWth, ATS begins to provide a lower Levelized Cost of Heat (LCOH) compared to optimized conventional thermal fields, demonstrating its potential applicability and efficiency in larger-scale CSP setups. Applying ATS to a 120 MWth Gemasolar-like plant further confirms its advantages, with 160 MWth emerging as the optimal enhancement point that boosted efficiency while lowering LCOH. ATS shows promise as an efficient, modular approach to scaling up power tower system.